2006
DOI: 10.1038/sj.emboj.7601329
|View full text |Cite
|
Sign up to set email alerts
|

Repression of ergosterol level during oxidative stress by fission yeast F-box protein Pof14 independently of SCF

Abstract: We describe a new member of the F‐box family, Pof14, which forms a canonical, F‐box dependent SCF (Skp1, Cullin, F‐box protein) ubiquitin ligase complex. The Pof14 protein has intrinsic instability that is abolished by inactivation of its Skp1 interaction motif (the F‐box), Skp1 or the proteasome, indicating that Pof14 stability is controlled by an autocatalytic mechanism. Pof14 interacts with the squalene synthase Erg9, a key enzyme in ergosterol metabolism, in a membrane‐bound complex that does not contain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 54 publications
2
23
0
Order By: Relevance
“…It has been demonstrated that the deletion of single genes in the ergosterol synthesis pathway rendered yeast cells more susceptible to oxidative stress (Branco et al 2004; Thorpe et al 2004). In addition, H2O2 was found to repress the ergosterol biosynthesis pathway through Pof14, a new member of the Fbox protein family, which binds and decreases the activity of the squalene synthase ERG9, a key enzyme in ergosterol metabolism, leading to a decrease of the total cellular ergosterol levels in Schizosaccharomyces pombe (Tafforeau et al 2006). Modulation of sterol level plays, therefore, a key role in adaptation to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the deletion of single genes in the ergosterol synthesis pathway rendered yeast cells more susceptible to oxidative stress (Branco et al 2004; Thorpe et al 2004). In addition, H2O2 was found to repress the ergosterol biosynthesis pathway through Pof14, a new member of the Fbox protein family, which binds and decreases the activity of the squalene synthase ERG9, a key enzyme in ergosterol metabolism, leading to a decrease of the total cellular ergosterol levels in Schizosaccharomyces pombe (Tafforeau et al 2006). Modulation of sterol level plays, therefore, a key role in adaptation to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, binding of Pof14 to Skp1 may promote the degradation of Pof14 itself. In wild-type cells, Pof14 has a half-life of 20 to 40 min, but in temperature-sensitive mutants of Skp1, Pof14 is stable for at least 60 min (193). Whether this stabilization is due to defective assembly of Skp1 and Pof14 into an SCF complex for self-ubiquitination is not known.…”
Section: Pof14: An F-box Protein That Inhibits Ergosterol Synthesismentioning
confidence: 97%
“…Transcription of POF14 is induced after treatment with hydrogen peroxide, and deletion of POF14 decreases viability after hydrogen peroxide treatment (193). Decreased viability was not observed upon deletion of the F-box domain, suggesting that binding of Pof14 to Skp1 is not required for peroxide resistance.…”
Section: Pof14: An F-box Protein That Inhibits Ergosterol Synthesismentioning
confidence: 98%
See 1 more Smart Citation
“…Immunoprecipitations were performed as described previously (20). In short, cells were disrupted with a Fastprep (MP Biochemical), and proteins were precipitated on appropriately coated Dynabeads (Invitrogen) following the instructions of the manufacturer (38). Cdc2 was precipitated using p13-Suc1 beads (Upstate Biotechnology).…”
Section: Methodsmentioning
confidence: 99%